Inside Women's Representative General Election - Awis Alhkarni; Wendra Yunaldi; Erry Gusman (Sahabat Publikasi, 2023)
Talking about women's rights in politics and democracy in Indonesia, it has actually been around for a long time since Indonesia became independent through the provisions of Article 27 paragraph (1) of the 1945 Constitution which stipulates that,